Adaptive components of tolerance to salinity in a saline desert grass Lasiurus scindicus Henrard. Issue 3 (30th December 2014) - Naz, Nargis; Batool, Riffat; Fatima, Sana; Hameed, Mansoor; Ashraf, Muhammad; Ahmad, Farooq; Ahmad, Muhammad Sajid Aqeel
Abstract: Five differently adapted natural populations of the native salt desert grass Lasiurus scindicus Henrard from Lesser Cholistan Desert (Pakistan) in South Punjab of east central Pakistan, were evaluated to examine their mechanism of adaptation to saline stress based on some key morpho–anatomical and physiological characteristics. Five ecotypes were collected from one saline site, two moderately saline sites, and two highly saline sites. Anatomical adaptations in each ecotype critically supported the physiological, but the adaptations were of specific nature depending on the type of each site's normal habitat conditions. Higher salinities resulted in increased Na +, Cl −, Mg 2+, Ca 2+ and K + content in root and shoot. At root level, some specific structural modifications like increased sclerification in cortical and pith regions, endodermal thickness, and number and size of xylem vessels are vital for water conservation under osmotic stress. Several characteristics were promising for increasing the plants ability to deal with osmotic stress, including at the stem level, increased sclerification, stem area, cortical region thickness and vascular bundle area, and at the leaf level, significant structural modifications such as leaf thickness, epidermal thickness, sclerenchymatous area, cortical area, metaxylem area and bulliform cell area were promising. All these may contribute towards water conservation, which ultimately account for ecotype survival under saline–induced physiological droughts.